2016
DOI: 10.1111/jcpp.12661
|View full text |Cite
|
Sign up to set email alerts
|

Telephone‐assisted self‐help for parents of children with attention‐deficit/hyperactivity disorder who have residual functional impairment despite methylphenidate treatment: a randomized controlled trial

Abstract: The TASH program enhances effects of methylphenidate treatment in families who complete the intervention. The discontinuation rate of about 30% and comparison between completing and discontinuing families suggest that the program may be more suitable for families with a higher educational level and fewer additional stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 33 publications
1
64
1
1
Order By: Relevance
“…Parent TASH programmes similar to that used in the present study have already been shown to reduce behaviour problems in preschool-and school-age children (e.g. [30,[32][33][34]). For the current study, the parent booklets were revised and adapted to address the specific needs of families of preschool children.…”
Section: Telephone-assisted Self-help (Tash)mentioning
confidence: 90%
See 1 more Smart Citation
“…Parent TASH programmes similar to that used in the present study have already been shown to reduce behaviour problems in preschool-and school-age children (e.g. [30,[32][33][34]). For the current study, the parent booklets were revised and adapted to address the specific needs of families of preschool children.…”
Section: Telephone-assisted Self-help (Tash)mentioning
confidence: 90%
“…An effectiveness study on a TASH intervention for parents of 6-12-yearold children with ADHD found a significant reduction of ADHD and comorbid symptoms under routine care conditions [32]. Moreover, TASH for parents was found to enhance effects of methylphenidate treatment in a sample of children with ADHD [33]. Interestingly, behavioural and non-behavioural TASH interventions seem to have similar effects [34].…”
Section: Introductionmentioning
confidence: 99%
“…In online-based self-help studies [15,16], effect sizes are in the lower to medium range (mostly 0.30 ≤ d ≤ 0.70). Telephone-assisted self-help for parents on the basis of booklets has been found to have moderate effects (0.33 ≤ d ≤ 0.59) [10]. For a comparison of two active conditions (WASH vs. WASH+SUPPORT), rather low to most moderate effects are expected (d = 0.30).…”
Section: Planned Sample Size and Power Calculationsmentioning
confidence: 96%
“…Media-applied PMT may help to overcome this structural lack of therapeutic supply as well as the structural barriers to attending and continuing face-to-face parent training, such as time and work commitments [9]. Telephone-assisted self-help interventions have been found to address some of these barriers and, furthermore, to be effective in the treatment of externalizing behavior problems [10,11] and to be superior to treatment as usual [12]. Although studies have evaluated internet-based treatments for patients with different disorders [13], research on internet-based self-help for caregivers of children with ADHD is rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation